Specific assessment of BCR-ABL transcript overexpression and imatinib resistance in chronic myeloid leukemia patients - Bianchini, Michele (2009)
Imatinib mesylate has proven to be the most effective treatment in chronic myeloid leukemia. Nevertheless, imatinib resistance has raised concern and prompted interest in additional strategies to achieve disease eradication. Resistance to imatinib is mainly associated with three mechanisms: acquired mutations in the kinase domain of BCR-ABL protein, genetic amplification, and transcript overexpression of BCR-ABL rearrangement. Therefore an accurate assessment of resistance mechanism is particularly important to improve strategies to overcome resistance. In order to determine overexpression of BCR-ABL, we propose a method that correlates quantitative real time PCR and fluorescence in situ hybridization data from the same peripheral blood sample. The ratio between both methodologies permits to calculate the expression index (EI) for each patient. EI estimates the rate of BCR-ABL transcription per rearrangement. The median EI value, including all cases (n = 123), was 0.288; those cases (n = 13) included in percentile 90 showed an increment of EI above 1 Log (>2.88) with respect to the median value and were considered as cases with overexpression. We also evaluated the EIs using receiver operating characteristics curve; choosing an EI cutoff of 1.836 we obtained a sensitivity of 95% and a specificity of 61%. Using this EI cutoff value, more patients (n = 17) were included in the overexpression group. Patients within this group were resistant to imatinib and also showed a worse overall survival if compared with the remaining. © 2009 Blackwell Munksgaard.